A study of factors affecting job performance of employees' at Malaysia Department of Insolvency, Putrajaya / Siti Zulaikha Md Zahidi - Md Zahidi, Siti Zulaikha (2014)
The present study examined associations between employees' and their job performance in Malaysia Department of Insolvency, Putrajaya. Job performance and the workplace is related to employees' for many years. Particular consideration that might affected employees' job performance was been identified including their distance from home to workplace, workplace, and vehicle, condition. Additionally, the researcher are more focus to increase productivity, reduce absenteeism, and maximize the motivation value toward employees' in Malaysia Department of Insolvency. A study of job performance of employees' in Malaysia Department of Insolvency will give many input and information to the researcher. The data were analyzed using SPSS version 20.